An Investigation Study on Optimizing Enterprise Resource Planning (ERP) Implementation in Emerging Public University: Al Baha University Case Study - Moh’D Suliman Shakkah; Khaled Alaqeel; Ali Alfageeh; Rahmat Budiarto (Institute of Advanced Engineering and Science, 2016)
This project investigates the correlation between the organizational readiness in Albaha University (ABU) and the respective Critical Success Factors (CSFs) with regards to the Enterprise Resource Planning (ERP) implementation. The investigation also considers some suggestions to improve the ABU’s ERP systems and roadmap towards the self –development strategy and reduce vendor-dependency. A survey regarding ERP to the end-user, expert and developer in ABU was conducted. The analysis of the results in this work confirmed with the results of an existing work. The four significance success factors: Project Management, Business Process Re-engineering (BPR), System Integration, and Training and Education are recommended to be adopted to assure the smooth adoption of ERP at Albaha University